МАГНІТОМЕТРИЧНІ ПЕРЕТВОРЮВАЧІ ІНФОРМАЦІЙНИХ ПРИСТРОЇВ КЕРУВАННЯ РУХОМИМИ ОБ’ЄКТАМИ - Смирний, М.Ф.; Полив’янчук, А.П. (Інститут електродинаміки НАН України, Київ, 2020)
Based on a two-dimensional potential problem, which is described by differential equations of the elliptical type, analytical expressions of orthogonal components of the tension of the outer magnetic field from the pole of the rod permanent magnet. These expressions are used as informative parameters when constructing magnetometric converters on the base of the bar permanent magnet and digital sensors of Hall. Presented a structural diagram and a diagram of the work of the proposed information device for the management of a moving object to determine the direction of the movement of one object relative to the other and the decrease in their mutual speed in the surroundings of the exact stop. References 12, figures 6.